An Analysis of Takwim Hijriah Khairiah in the Context of Historical Development of the Malaysian Hijri Calendar - Abdul Wahab, Raihana; Abdul Niri, Mohammaddin; Faid, Muhammad Syazwan; Mohd Nawawi, Mohd Saiful Anwar; Nizam, Nurul Kausar (Journal of Al-Tamaddun, 2025)
The evolving use of various criteria in the Malaysian Hijri calendar reflects its historical development and dynamism. A prominent local Islamic astronomer, Md Khair Md Taib has contributed significantly to this development, particularly through his seminal work, Takwim Hijriah Khairiah (THK). This study analyses his contributions by evaluating the methodologies employed in THK, focusing on Hijri-Gregorian date synchronization, and examining his approach in balancing traditional Islamic astronomical practices with contemporary precision standards. A comparative analysis assessed the accuracy of Md Khair Md Taib’s methods against modern computation using Accurate Time software. The findings highlight key contributions, such as the creation of user-friendly astronomical tables and the adaptation of the Istilahi method, which bridges traditional Islamic astronomy with practical applications for the Muslim community. The study also emphasizes the ongoing relevance of THK as a technical resource and a cultural milestone in the historical development of the Malaysian Hijri calendar. By integrating traditional and modern practices, Md Khair Md Taib’s work remains an invaluable reference for researchers, policymakers, and the broader Muslim community. This review underscores the importance of revisiting foundational texts like THK to preserve and advance the intellectual heritage of Islamic astronomy in Malaysia and beyond.